Surface Treatment of Glass Vials for Lyophilization: Implications for Vacuum-Induced Surface Freezing - Francesco Regis; Andrea Arsiccio; Erwan Bourlès; Bernadette Scutellà; Roberto Pisano (MDPI AG, 2021)
Freeze-drying is commonly used to increase the shelf-life of pharmaceuticals and biopharmaceuticals. Freezing represents a crucial phase in the freeze-drying process, as it determines both cycle efficiency and product quality. For this reason, different strategies have been developed to allow for a better control of freezing, among them, the so-called vacuum-induced surface freezing (VISF), which makes it possible to trigger nucleation at the same time in all the vials being processed. We studied the effect of different vial types, characterized by the presence of hydrophilic (sulfate treatment) or hydrophobic (siliconization and TopLyo Si-O-C-H layer) inner coatings, on the application of VISF. We observed that hydrophobic coatings promoted boiling and blow-up phenomena, resulting in unacceptable aesthetic defects in the final product. In contrast, hydrophilic coatings increased the risk of fogging (i.e., the undesired creeping of the product upward along the inner vial surface). We also found that the addition of a surfactant (Tween 80) to the formulation suppressed boiling in hydrophobic-coated vials, but it enhanced the formation of bubbles. This undesired bubbling events induced by the surfactant could, however, be eliminated by a degassing step prior to the application of VISF. Overall, the combination of degasification and surfactant addition seems to be a promising strategy for the successful induction of nucleation by VISF in hydrophobic vials.